Adding character: The role of destination mascots in tourism development. (June 2021) - Radomskaya, Valeriya; Pearce, Philip L.
Abstract: This study explores the use of destination mascots in tourism development. It steps away from the traditional investigation of yuru kyara by focusing on a wider range of anthropomorphic messengers. By mapping the historical trajectory of mascots, the researchers isolate a special subcategory of anthropomorphic characters: destination mascots. Destination mascots are introduced as a new tourism construct and a distinct type of marketing activity. This paper aims to develop and promote the term destination mascot in tourism literature. It describes the many facets of destination mascots and catalogues five distinct functions mascots can carry out for their destinations: mascots as place identity markers, cultural constructs, bonding tools, social engagement tools, and information carriers. Supplemented with multiple examples from past and present literature, this study deepens and broadens our understanding of mascot culture. It brings into view many avenues that invite further exploration.